First Complete Genome Sequences of Genogroup VI Porcine Sapoviruses - Oka, Tomoichiro (American Society for Microbiology, 2014)
Sapoviruses, members of the family Caliciviridae, are genetically diverse and divided into multiple genogroups. Only a few complete genome sequences of animal strains are available. We report the first complete genome sequences of genogroup VI sapoviruses, those of strains JJ674 and JJ681, isolated from fecal samples from diarrheic pigs.